De las sinapsis biológicas a las sinapsis sociales creencias en tuberculosis - Botero Carvajal, Alejandro (Universidad Santiago de Cali, 2020)
Introduction: Tuberculosis (TB) is the world's most lethal infectious disease. Actions to prevent and treat TB depend on beliefs about it. The purpose of the paper is to understand the emergence of belief from the perspective of cognitive neuroscience and the role of belief in tuberculosis. Methodology: Narrative review of literature. From a methodological point of view, articles that met the following inclusion criteria were selected: a) published between 1970 and 2017; b) judge beliefs about tuberculosis; c) be retrieved in full text from a peer-reviewed journal; and d) published in English or Spanish. Results: Beliefs about tuberculosis mediate the relationship between health and disease. In different contexts and human groups. Patients and health personnel have opposing theories about TB: intuitive theories in the first case and scientific theories in the second case Discussion: Cultural sensitivity to disease to reveal erroneous beliefs, coupled with a high level of knowledge on the part of health personnel, is a powerful tool for tackling TB disease.